Postoperative Epidural Hematomas in the Lumbar Spine. Issue 9 (November 2015) - Unknown
Abstract : Postoperative epidural hematomas are rare complications following lumbar spine surgery, but if they are not quickly identified and treated they can lead to permanent neurological deficits. Epidural hematomas occur in approximately 0.10%–0.24% of all spine surgeries, and despite the fact that multiple large studies have been performed attempting to identify risk factors for this complication, there is still significant debate about the effect of subfascial drains, postoperative anticoagulation, and antiplatelet medication on the incidence of postoperative hematoma. The purpose of this manuscript is to review the epidemiology, etiology, diagnosis, and treatment of patients who develop a postoperative lumbar epidural hematoma.